Pomegranate (Punica granatum) By-Product Extract Influences the Oxylipids Profile in Primary Bovine Aortic Endothelial Cells in a Model of Oxidative Stress - Ciampi, Francesco; Gandy, Jeffery; Ciliberti, Maria Giovanna; Sevi, Agostino; Albenzio, Marzia; Santillo, Antonella (Frontiers in Animal Science, 2022)
Aerobic metabolism produces reactive oxygen species (ROS) as natural by-product that can play a significant role in cell signaling and homeostasis. Excessive and uncontrolled production of ROS, however, can lead to oxidative stress that causes damage to immune cells and is related to several diseases in dairy cattle. Endothelial cells are essential for optimal immune and inflammatory responses but are especially sensitive to the damaging effects of ROS. Accordingly, investigating antioxidant strategies that can mitigate the detrimental impact of ROS on endothelial functions could impact compromised host defenses that lead to increased disease susceptibility. The objective of this study was to test the antioxidant effect of different concentrations (20, 40, 60, 80 μg/mL) of pomegranate by-product extract (PBE) on bovine aortic endothelial cells (BAECs). A model of oxidative stress was developed using in vitro exposure of BAEC to 2,2'-Azobis (2-amidinopropane) dihydrochloride (AAPH) to induce the formation of ROS. The BAEC were then analyzed for cell viability, ROS production, fatty acids profile, and oxylipids formation. The BAECs viability did not change after different concentrations of PBE and remained up to 80% over control; whereas, intracellular ROS showed a reduction passing from 20% to 50% with increasing PBE concentration from 20 to 80 μg/mL, respectively. The PBE extract clearly demonstrated efficacy in reducing the concentrations of pro-inflammatory oxylipids with a concomitant enhancement of anti-inflammatory oxylipids. In particular, the pro-inflammatory 13-hydroxyoctadecadienoic acid and its derived anti-inflammatory 13-hydroperoxoctadecaienoic acid were found lower and higher, respectively, in PBE+AAPH treated cells than AAPH treatment. Data from the present study supports in vivo future experimental use of pomegranate by-product extract to study its potential beneficial effect against oxidative stress conditions in dairy cattle.